SCIENTIFIC THEORETICAL BASIS OF TEACHING YOUNG STUDENTS TO DESCRIBE LANDSCAPE COMPOSITION - Ilkhom Bakhriev, (European International Journal of Pedagogics, 2023)
This article describes the scientific theoretical basis of teaching future fine art teachers to describe landscape composition and its development history, the issues of using landscape views in composition classes for students.